Perseverance of natural Law in Cayetano Betancur (2011)
The article inquires about the reflection on law develop by Cayetano Betancourt (Copacabana, Antioquia, 1910 - Bogotá, 1982). Cayetano was a representative of the generation of thinkers who carry out the “normalization” of philosophical studies in Colombi